DECENTRALIZED DATA EXCHANGE PROTOCOL FOR THE MANUFACTURING INDUSTRY (Nonconventional Technologies Review, 2023)
This article proposes a secure and transparent data exchange protocol that addresses the challenges of data privacy and security in the manufacturing industry. Sharing data among stakeholders is essential for optimizing production processes, enhancing product quality, and reducing costs. However, data privacy and security concerns hinder achieving these objectives, leading to missed opportunities and inefficiencies. This paper suggests utilizing blockchain technology, smart contracts, tokenization, and interoperability to develop a data exchange protocol that ensures security and privacy. The proposed protocol enables manufacturers to securely and transparently exchange collected and stored data while preserving privacy. The article includes a detailed technical description of the protocol and discusses its potential applications in manufacturing.
Keywords: manufacturing; web3; blockchain; data; privacy; exchange; protocol